2013
DOI: 10.1063/1.4796149
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous exchange bias in a nanocomposite of BiFeO3-Bi2Fe4O9

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
2
10
1
Order By: Relevance
“…The reported high value of SEB from Bi 2 Fe 4 O 9 -BiFeO 3 as compared to Cr 2 O 3 NRs is due to the inter-coupling between the log-range ordered FM and AFM spins at the interface. 32,33 Furthermore, the p-type and ntype M(H a ) loops measured in the ZFC mode are almost symmetric in nature and exhibit a similar value for SEB, which is within the experimental measurement error. The observed similar value of H SEB in both eld direction indicate shis in M(H) loops are not experimental artifacts, but rather an intrinsic property of Cr 2 O 3 NRs.…”
Section: Morphological and Stoichiometric Analysissupporting
confidence: 73%
See 1 more Smart Citation
“…The reported high value of SEB from Bi 2 Fe 4 O 9 -BiFeO 3 as compared to Cr 2 O 3 NRs is due to the inter-coupling between the log-range ordered FM and AFM spins at the interface. 32,33 Furthermore, the p-type and ntype M(H a ) loops measured in the ZFC mode are almost symmetric in nature and exhibit a similar value for SEB, which is within the experimental measurement error. The observed similar value of H SEB in both eld direction indicate shis in M(H) loops are not experimental artifacts, but rather an intrinsic property of Cr 2 O 3 NRs.…”
Section: Morphological and Stoichiometric Analysissupporting
confidence: 73%
“…5(a) Slightly lower values of H SEB are obtained aer the n-type measurements than those of the p-type. Maity et al 32,33 reported H SEB of À850 Oe and +615 Oe aer p-and n-type hysteresis loop measurements from the Bi 2 Fe 4 O 9 -BiFeO 3 FM/ AFM system, respectively. The slight difference observed in the behavior of SEB eld obtained using the p-and n-type protocols is a common phenomenon.…”
Section: Morphological and Stoichiometric Analysismentioning
confidence: 99%
“…This sample is free from any secondary impurity phase such as Bi 2 Fe 4 O 9 . In our earlier work [14,15], we showed that sizable exchange bias (both spontaneous and conventional) could be observed in systems where Bi 2 Fe 4 O 9 is present by ∼6 vol%. In the present case, no exchange bias could be observed (inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Different low dimensional BiFeO 3 systems, such as nanoparticles and nanotubes are known to display weak ferromagnetic behaviour at room temperature and spin glass type behaviour at low temperature [15][16][17]. The EB and its origin in BiFeO 3 based systems are in discussion in recent times [11,15,[18][19][20][21][22][23]. It was found to persist at room temperature in some nano-dimensional systems consisting BiFeO 3 and was ascribed to the spin pinning at the interface between the AFM and weak FM layers present in those structures [15].…”
Section: Introductionmentioning
confidence: 99%
“…[23]. Recently, Maity et al on the other hand found EB only when a SSG-type structure is formed at low temperature in BiFeO 3 -Bi 2 Fe 4 O 9 nanostructures and the phenomenon was linked to pinning of glassy spins to the remaining antiferromagnetic spins [11,21]. A skin layer different from its bulk is also reported in single crystalline BiFeO 3 which influences several of its properties including the EB [24].…”
Section: Introductionmentioning
confidence: 99%